A concurrent approach to the periodic event scheduling problem. (September 2020) - Borndörfer, Ralf; Lindner, Niels; Roth, Sarah
Abstract: We introduce a concurrent solver for the periodic event scheduling problem (PESP). It combines mixed integer programming techniques, the modulo network simplex method, satisfiability approaches, and a new heuristic based on maximum cuts. Running these components in parallel speeds up the overall solution process. This enables us to significantly improve the current upper and lower bounds for all benchmark instances of the library PESPlib. Highlights: A concurrent solver for the Periodic Event Scheduling Problem (PESP). Combines many state-of-the-art techniques in periodic timetabling. Computes current best primal and dual bounds for all PESPlib instances.